Zmiany w marketingowych procesach planowania innowacji produktowych pod wpływem globalizacji (na przykładzie dóbr trwałego użytku) - Wiechoczek, Joanna (Changes in Marketing Processes of Product Innovation Planning Affected by Globalization (on the Example of Durable Goods), 2006)
Changing external and internal conditions for durable goods manufacturers cause them to concentrate on winning and maintaining their clients, while taking measures to reduce costs of their activities. This requires very precise definition of a target market, constant innovative processes related to products development as well as effective offer differentiation. The result is creation of new marketing concepts in the area of product innovation planning. They include among others simultaneous marketing (concerning the whole process of innovation development) and lateral marketing (used in generating and developing of a new product idea). Lateral marketing fosters true creativity, including product innovation. It provides manufacturers with greater possibilities to create new product category or subcategory, which makes the company to win and maintain for a longer period of time the leading position therein; additionally, so called multisectoral products often result from its application.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 196-207